Preaching, truth, and colonial subject: genealogies of obedience in Mapuche context - Lepe-Carrión, Patricio (2016)
This paper examines modalities of Jesuit preaching that are part of the scheme of Christian subjectivity, and that come into play with strategies of conquest, expansion and exploitation in the Kingdom of Chile during the seventeenth century. It intends a reading of the colonial past, and of colonial power relations embedded in technologies of the self. This reading is part of a Fondecyt Initiation Project nº11140804, whose object of analysis are the effects of depoliticization in Intercultural Education in the recent, post-dictatorship decades. The axis that guides this work is to reflect on how the core of the Mapuche subjectivity (weichafe) has for centuries been the focus of interest in policies or practices of imperial domination.